GABAρ selective antagonist TPMPA partially inhibits GABA-mediated currents recorded from neurones and astrocytes in mouse striatum. (February 2017) - Reyes-Haro, Daniel; Hernández-Santos, José Antonio; Miledi, Ricardo; Martínez-Torres, Ataúlfo
Abstract: The neostriatum plays a central role in motor coordination where nerve cells operate neuronal inhibition through GABAergic transmission. The neostriatum expresses a wide range of GABA-A subunits, including GABAρ1 and ρ2 which are restricted to a fraction of GABAergic interneurons and astrocytes. Spontaneous postsynaptic currents (sPSCs) evoked by 4-aminopyridine (4-AP) were recorded from neurones of the dorsal neostriatum, and their frequency was reduced > 50% by the selective GABAρ antagonist (1, 2, 5, 6-Tetrahydropyridine-4-yl) methylphosphinic acid (TPMPA). Additionally, we recorded GABA evoked currents from astrocytes in vitro and in situ . Astrocytes in vitro showed modulation by pentobarbital and desensitization upon consecutive applications of GABA. However, modulation by pentobarbital was absent and no significant desensitization was detected from astrocytes in situ . Moreover, TPMPA-sensitive GABA-currents that were insensitive to bicuculline were also recorded from astrocytes in situ, consistent with our previous study where GABAρ expression was demonstrated. Finally, we assessed the mRNA expression of GABAρ3, through different stages of postnatal development; double immunofluorescence disclosed GABAρ3 expression in calretinin-positive interneurons as well as in astrocytes (>70%). These results add new information about the participation of GABAρ subunits in neostriatal interneurons and astrocytes. Highlights: The effect of TPMPA on neostriatal neurones and astrocytes was investigated. Spontaneous postsynaptic currents recorded in neurones were reduced > 50% by TPMPA. GABA-A-mediated currents recorded in astrocytes showed a TPMPA-sensitive component. More than 70% of calretinin neurons or astrocytes are immunoreactive to GABAρ3.